2017
DOI: 10.1021/acsami.7b11947
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial 3D Porous Scaffolds Prepared by Additive Manufacturing and Breath Figures

Abstract: We describe herein a novel strategy for the fabrication of efficient 3D printed antibacterial scaffolds. For this purpose, both the surface topography as well as the chemical composition of 3D scaffolds fabricated by additive manufacturing were modified. The scaffolds were fabricated by fused deposition modeling (FDM) using high-impact polystyrene (HIPS) filaments. The surface of the objects was then topographically modified providing materials with porous surfaces by means of the Breath Figures approach. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…al, objects printed with the use of FDM are significantly less toxic than SLA-printed parts for living organisms [19]. FDM has already been successfully used for printing biomedical devices [20,21]. Additionally, a fast-growing open-source community provides access to expert solutions and knowledge in the use of FDM 3DPs, which further reduces costs and facilitates the use of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…al, objects printed with the use of FDM are significantly less toxic than SLA-printed parts for living organisms [19]. FDM has already been successfully used for printing biomedical devices [20,21]. Additionally, a fast-growing open-source community provides access to expert solutions and knowledge in the use of FDM 3DPs, which further reduces costs and facilitates the use of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…al, objects printed with the use of FDM are significantly less toxic than SLA-printed parts for living organisms [16]. FDM has already been successfully used for printing biomedical devices [17,18]. Additionally, a fast-growing open-source community provides access to expert solutions and knowledge in the use of FDM 3DPs, which further reduces costs and facilitates the use of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, an illustrative strategy of this approach was recently reported by Vargas-Alfredo et al [98] who reported a strategy that combines the use of high-impact polystyrene (HIPS) to fabricate 3D parts with surface functionalization methodologies to provide antimicrobial 3D objects. The scaffolds were first fabricated by FDM using commercially available HIPS filaments.…”
Section: Synthetic Polymers With Bactericidal Propertiesmentioning
confidence: 99%